Press-ekspress . Press-ekspress . Press Express . Пресс-экспресс - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Russian and foreign press review. Program discusses how political affiliation influences professional journalism. Contributors: Egorshev, Andrei (Anchor) Series description: Press reviews, interviews with journalists, presentations of magazines and newspapers. Обзор российской и зарубежной прессы. О влиянии политической направленности издания на работу журналистов. Создатели: Егоршев, Андрей (Ведущий/Ведущая) Описание серии: Обзор прессы, интервью с журналистами, представление журналов и газет.